STUDENT’S PERCEPTION ABOUT BUILDING SELF-FULFILMENT OF ISLAMIC BOARDING SCHOOL BASED ON ARTIFICAL INTELEGENCE IN PMDG GONTOR DARUSSALAM (International Conference on Social and Islamic Studies, 2022)
This article draws on the fact that pesantren have been widely built in the country, as the oldest educational base ever in Indonesia. So that various dynamics have been experienced according to current developments. Nevertheless it is as a social force that grows and develops within society. Pesantren has its own character and concentration of scientific development, and has a very significant self-defense mechanism (stuggle to survive) in building independence. So that it is not excessive that various efforts have been made to be able to build independence, including; develop agricultural businesses, agriculture, plantations, cooperatives, television, radio printing and various other productive businesses. This is adjusted to the potential of the area owned by each area occupied by the pesantren itself. Furthermore, the objectives of this study are: (1) Describe the various productive business activities of students that have been developed by pesantren in building their independence. (2) Describe artificial intelligence used by students as a new force in the development of pesantren businesses to build institutional independence. (3) Connecting artificial intelligence with pesantren efforts in developing institutional independence. This research was located in Ponorogo, East Java. The selection of Gontor as a research location is because, Gontor has a tradition of developing institutional independence that has been tested by more than 90 years. So that there have been many business developments that have been carried out and successfully maintain the independence of their institutions. Furthermore, as many as 267 students as a population and a sample of 159 students as a sample in this study.  The technique of measuring the sample magnitude using the Slovin formula (n=N/1+N.e2). Data collection techniques are carried out by random sampling. Data analysis techniques with product momment (pearson correlation). The results of the research findings: (1) Various conventional businesses have been (agriculture, plantations, fisheries and so on) have been developed to build the independence of the institution in Gontor. (2) There are technology-based businesses that have also been developed in supporting the development of business units run by "digital-based MSMEs". (3) There is a positive and significant relationship between students' perceptions of artificial development of intelligence and the independence of institutions in islamic boarding schools, especially Gontor. Thus, this research proves that technological advances need to be addressed wisely by pesantren and not make them enemies but a medium for developing the independence of pesantern institutions, without having to remove the identity of the pesantren itself.